2023
DOI: 10.1002/admi.202300535
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Optimization of High‐Quality Epitaxial Lithium Niobate Thin Films by Chemical Beam Vapor Deposition: Impact of Cationic Stoichiometry

Anna L. Pellegrino,
Estelle Wagner,
Francesca Lo Presti
et al.

Abstract: Lithium niobate is a material of special interest for its challenging functional properties, which can suit various applications. However, high quality 200‐mm LixNb1‐xO3 thin film grown on sapphire substrate have never been reported so far which limits these potential applications. This paper reports the efficient optimization of high quality LiNbO3 thin film deposition on sapphire (001) substrate through chemical beam vapor deposition in a combinatorial configuration. With this technique, flow ratio of Li/Nb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…The presence of C is attributed to adventitious contamination, while the low percentage of F suggests some fluorine contamination from the β-diketonate ligands (as shown in Table 3 ). In the region reported in Figure 6 , we observe the presence of Nb 4s at 60.2 eV and Li 1s at 54.7 eV, in accordance with literature data [ 40 ]. For the quantitative evaluation, a Gaussian shape was used for the Li 1s peak, while an asymmetric Gaussian–Lorentzian shape was used for the Nb 4s peak [ 72 , 73 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The presence of C is attributed to adventitious contamination, while the low percentage of F suggests some fluorine contamination from the β-diketonate ligands (as shown in Table 3 ). In the region reported in Figure 6 , we observe the presence of Nb 4s at 60.2 eV and Li 1s at 54.7 eV, in accordance with literature data [ 40 ]. For the quantitative evaluation, a Gaussian shape was used for the Li 1s peak, while an asymmetric Gaussian–Lorentzian shape was used for the Nb 4s peak [ 72 , 73 ].…”
Section: Resultssupporting
confidence: 91%
“…Concerning the methods employed thus far to deposit thin films of LiNbO 3 , the most commonly utilized techniques include liquid phase epitaxy (LPE) [ 39 ], chemical beam vapor deposition [ 40 ], metalorganic chemical vapor deposition (MOCVD) [ 16 , 41 , 42 , 43 , 44 ], pulsed layer deposition (PLD) [ 45 , 46 ], molecular beam epitaxy (MBE) [ 47 , 48 ], RF sputtering [ 49 , 50 , 51 ], atomic layer deposition (ALD) [ 52 , 53 ], and sol–gel deposition [ 54 , 55 ]. In the early 1990s, Nashimoto et al reported the sol–gel deposition of epitaxial LN films from lithium ethoxide and niobium pentaethoxide with varying water contents on sapphire substrates [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…To ascertain the direction of the phase shift, we conducted M-line spectroscopy on a thick film (> 5µm) before and after immersion in water [13]. The results revealed a decrease in the effective RI for both TE and TM polarizations after the film was immersed in water.…”
Section: Refractive Index Variation With Humiditymentioning
confidence: 99%